Prevalence of respiratory virusin a selected population of children with asthma exacerbation (2012)
Determine the prevalence of five respiratory viruses in a selected population of Colombian children with asthma exacerbation and a possible association between their presence and the patient's age, the severity of the exacerbation, medication used, admission to ICU and hospitalization. Also, assess a possible relationship between the variables mentioned previously and Rhinovirus's subtypes as well as Respiratory Syncytial Virus's viral load.